Digital Health Services in Managing People Living with Diabetes - Gupta, P.P.; Maskey, R. (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
In the recent world, more than 450 million people have diabetes. There are several types of diabetes and among them common are Type 1 DM in which the body cannot produce Insulin, Type 2 DM in which body cannot properly use insulin and Gestational Pregnancy related Diabetes. For diabetic patients, failure to treat or manage it can lead a serious complications like blindness, renal failure, heart attack and lower limb amputation. The burden of diabetes in patients are more acute in low middle income countries where nearly 80 % people lived with diabetes.